Pengaruh GoFood terhadap Omzet Penjualan Pedagang Bakso - Fayzan Rabbani; Kyla Thahira; Hikmah Habibah Harahap; Zainarti . (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The rapid growth of digital food delivery platforms, particularly GoFood, has significantly transformed the distribution and marketing patterns of micro, small, and medium enterprises (MSMEs) in the culinary sector. This study aims to analyze the effect of using GoFood services on the sales turnover of bakso vendors. The research employs a quantitative approach using survey methods, with data collected through structured questionnaires distributed to bakso vendors registered as GoFood partners. The results indicate that the utilization of GoFood has a positive and significant effect on increasing the sales turnover of bakso vendors. However, this increase in turnover is accompanied by higher operational costs, particularly in the form of platform commission fees. These findings suggest that while GoFood serves as an effective tool for expanding market reach and increasing sales volume, it also requires vendors to manage costs and pricing strategies carefully to ensure business sustainability.